Load‐Bearing Capacity of Monolithic Zirconia Fixed Dental Prostheses Fabricated with Different Connector Designs and Embrasure Shaping Methods. Issue 1 (3rd December 2018) - Bakitian, Fahad; Seweryniak, Przemek; Papia, Evaggelia; Larsson, Christel; Vult von Steyern, Per
Abstract: Purpose: To investigate the load‐bearing capacity and failure mode of monolithic zirconia fixed dental prostheses (FDPs) fabricated with different connector designs and embrasure shaping methods. Materials and Methods: Seventy four‐unit zirconia FDPs (with two premolar pontics) were fabricated and divided into seven groups (n = 10) according to the different connector designs gained by using different embrasure shaping methods. The groups were as follows: monolithic FDPs fabricated with sharp embrasures, monolithic FDPs fabricated with blunt embrasures, monolithic FDPs fabricated with blunt embrasures and no occlusal embrasures, two groups of monolithic FDPs fabricated with blunt embrasures and interproximal separations made with diamond discs at the soft stage and at the fully sintered stage, and monolithic FDPs fabricated with blunt embrasures and interproximal separation accentuated by localized porcelain build‐up. A final group was used as a control group, where fully veneered traditional zirconia FDPs were fabricated with default milling settings. The FDPs were artificially aged and loaded to fracture. Load to fracture and failure modes were analyzed by one‐way ANOVA, Tukey's post hoc test, and Fisher exact test (α = 0.05). Results: The FDPs fabricated with interproximal porcelain separation showed significantly the highest load to fracture (1038 N ± 82) of all groups ( p < 0.001), with no significant difference compared to the FDPs with no occlusal embrasures (934 N ± 175; p ˃ 0.29). The FDPs fabricated with blunt embrasures showed significantly higher load to fracture (873 N ± 115) compared to the FDPs in the control group (689 N ± 75) and the FDPs with sharp embrasures (417 N ± 87; p < 0.001). There were no significant differences between the FDPs with sharp embrasures (417 N ± 87) and the FDPs with interproximal disc separations (467 N ± 94; p ˃ 0.23). Failure mode of the FDPs fabricated with sharp embrasures and interproximal disc separations differed significantly compared to the FDPs in the other groups ( p < 0.001). Conclusions: Sharp embrasures and interproximal separations made with diamond discs significantly decrease the load‐bearing capacity of monolithic zirconia FDPs compared to FDPs made with blunt embrasures. Blunt embrasures in combination with localized porcelain build‐up produce FDPs with high load‐bearing capacity in relation to loads that might be expected under clinical use.